Décrire une ville pour affirmer une identité - Vincent Mahieu (Cahiers Mondes Anciens)
The religious character of Rome at the turn of the 4th and 5th centuries reveals an evolving face: new elements, related to the legitimacy acquired by Christianity, insert themselves into a traditional background marked by a certain continuity. This phenomenon, carved in stone, is expressed through language: through its various dimensions, including religion, the Vrbs is an object of discourse, sometimes not in tune with its material reality. With the support of conceptual tools drawn from social sciences, the present paper aims at analyzing how authors of that period (Rutilius Namatianus, Claudian, Prudentius, etc.) organize their discourse, according to their position. A mix of continuity and novelties, based on a spirit of consensus, direct confrontation or subtle alternatives, these discursive representations of space are involved in constructing identity and are, as such, key issues.